Proposal on creating an institutional administrative policy that allows participants in the spanish teaching-assistant program in france to have a meaningful contribution to french language learning in the modern language major - Ventura Amaya, Isaí Eliseo
The Modern Language major of the Foreign Language Department of the University of El Salvador was created by 2001 and launched officially at the end of the year 2002 as an institutional project that was supported by the local French Embassy. The main objective was to promote French language learning among Salvadoran university students to become proficient in French and English languages during the whole five-year program as well as giving the option to take part in the Spanish teaching- assistant program in France among others. By the year 2004, the linguistic assistants of the local French Embassy started promoting the exchange among the rising number of students of the Modern Language major in order to encourage them to turn out to be successful students to be taken into consideration to be part of the selection process to become language assistants in France. It is indispensable to mention that the first massive participation of the students of the Modern Language major in this exchange took place until the year 2005 when about thirteen students were selected to take part in the program. In the previous years some students of different majors of the University of El Salvador participated in the selection process and later were selected as Spanish teacher-assistants to open the path for the students of the emerging major.